How old is Miss Havisham? : Age and Gender Performances in Great Expectations and Sunset Boulevard - Miquel Baldellou, Marta (Age, Culture, Humanities: An Interdisciplinary Journal, 2018)
The characters of Miss Havisham in Charles Dickens’s Great Expectations and Norma Desmond in Billy Wilder’s Sunset Boulevard address a matrix of age, gender, and performance through significant points of intertextuality. They epitomize what Anne Morey has referred to as “the elegiac female grotesque” to depict older women’s overstated performances of age and gender; these performances can be interpreted as ambivalent, insofar as they personify the abjection of female aging, but they also subvert the dictates of age imposed on women. Given the transformative quality of performance that characterizes both age and gender, critics such as Deborah Jermyn have argued for the need to revisit representations of aging women with special insight into their performative and, ultimately, transformative dimensions. With this purpose in mind, this article analyzes the performances of age and gender that these two classic characters exhibit, examines how they respectively overstate age and deny it, and reveals how they represent an ambivalent dimension of age performativity—acting age and acting against age—which still prevails in current cultural representations of female aging.